Impact of Hemodialysis on Procedural Outcomes of Percutaneous Coronary Intervention for Chronic Total Occlusion: Insights From the Japanese Multicenter Registry. Issue 10 (11th October 2017) - Nakachi, Tatsuya; Kohsaka, Shun; Yamane, Masahisa; Muramatsu, Toshiya; Okamura, Atsunori; Kashima, Yoshifumi; Matsuno, Shunsuke; Sakurada, Masami; Kijima, Mikihiko; Tanabe, Masaki; Habara, Maoto
Abstract : Background: Among patients treated with percutaneous coronary intervention for chronic total occlusion (CTO‐PCI), patients on long‐term hemodialysis are at significantly high risk for cardiovascular mortality and morbidity. However, clinical or angiographic predictors that might aid in better patient selection remain unclear. We aimed to assess the acute impact of hemodialysis in patients who underwent CTO‐PCI. Methods and Results: The Retrograde Summit registry is a multicenter, prospective registry of patients undergoing CTO‐PCI at 65 Japanese centers. Patient characteristics and procedural outcomes of 4749 patients were analyzed, according to the presence (n=313) or absence (n=4436) of baseline hemodialysis. A prediction model for technical failure among hemodialysis patients was also developed. The technical success rate of CTO‐PCI was significantly lower in hemodialysis than in nonhemodialysis patients (78.0% versus 89.1%, P <0.001). The rates of in‐hospital major adverse cardiac and cerebrovascular events were similar between the 2 groups (1.6% versus 0.9%, P =0.24). Irrespective of clinical/angiographic characteristics or previously developed scoring systems, hemodialysis independently predicted technical failure for CTO‐PCI. Among hemodialysis patients, predictors of technical failure were blunt stump (odds ratio 2.45, 95% confidence interval, 1.15–5.21, P =0.021), severe lesion calcification (odds ratio 2.50, 95% confidence interval, 1.19–5.24, P =0.015), and absence of diabetes mellitus (odds ratio 3.15, 95% confidence interval, 1.49–6.64, P =0.003). In hemodialysis patients without these predictors, the technical success rate was 96.2%. Conclusions: Hemodialysis is significantly associated with technical failure. Contemporary CTO‐PCI seems feasible and safe in selected hemodialysis patients.